The Saline Load Test is Effective at Diagnosing Traumatic Arthrotomies of the Wrist. Issue 2 (June 2019) - Gittings, Daniel J.; Fryhofer, George W.; Hast, Michael W.; Steinberg, David R.; Levin, L. Scott; Gray, Benjamin L.
Abstract : Background: The saline load test has previously been shown to be an effective tool to diagnose traumatic arthrotomies, but no studies have assessed the test's efficacy in the wrist. The purpose of this study was to investigate the amount of fluid required during a saline load test to detect intra-articular wrist involvement of traumatic wounds with high sensitivity. Methods: A cadaveric study was conducted using 7 thawed, fresh-frozen forequarter amputations from 7 different donors (3 male, 4 female). Specimen age (mean: 67.7 y, range: 52 to 80 y), laterality (1 right, 6 left), body weight (mean: 164.3 lbs, range: 100 to 223 lbs), and wrist range of motion (ROM) was assessed before testing. The wrist capsule was punctured with an 11-blade scalpel through the 6R radiocarpal portal site under fluoroscopic guidance to ensure the injury was intra-articular. A 19-G needle was then placed through the 3, 4 radiocarpal portal site and confirmed with fluoroscopy to ensure intra-articular placement. Normal saline was then injected at a steady rate into the 3, 4 radiocarpal portal site until extravasation of the saline was observed from the 6R radiocarpal arthrotomy site. The volume of saline required for extravasation from the 6R radiocarpal arthrotomy was recorded as the volume required to detect the arthrotomy. A plot of saline volumes (by percentile) was created, and a logarithmic distribution was calculated. A Wilcoxon rank-sum test was used to compare injection volumes between male and female specimens, and Pearson Coefficients were used to determine any correlations between injection volume and ROM. Results: The average amount of saline that resulted in extravasation was 4 mL (range: 2 to 7 mL). In order to identify 75%, 90%, 95%, and 99% of the simulated wrist arthrotomies, 5 (95% confidence interval: 3-7), 6 (4-9), 7 (4-10), and 9 (5-14) mL were required, respectively. Pretest ROM did not correlate with saline volume. Conclusions: This study demonstrates the efficacy of the saline load test in detecting traumatic arthrotomies of the wrist joint with 95% sensitivity after loading 7 mL of saline. Prompt and accurate diagnosis of traumatic arthrotomies is paramount to guide management and optimize postinjury outcomes.